Enhancing Investment Decisions Through Financial Literacy: The Mediating Role of Income in Medan's Community Using SEM-PLS Modeling - Hastalona, Dina (Manunggal Halim Jaya, 2024)
The objective of this research is to elucidate and analyze the extent to which foundational knowledge of investment products and financial analysis influences investment decisions in Medan, incorporating community income enhancement in Medan as a mediating variable. The subjects of this study are entities that utilize green energy, where the independent variables are the basic understanding of investment products and financial analysis, the dependent variable is the investment decision-making in Medan, and the intervening variable is the enhancement of community income in Medan. Data analysis employed the Structural Equation Modeling (SEM) technique utilizing SMART PLS 4.0 software. Data collection methods included questionnaires and observation. The research methodology applied was quantitative descriptive analysis utilizing the SEM method, where data processing with SEM was performed using PLS 4.0 application. The findings indicate that, partially, the variables of basic understanding of investment products and financial analysis significantly affect investment decisions and impact the enhancement of community income. Simultaneously, these variables influence investment decisions through the mediating variable of community income enhancement. A deeper understanding of investment products and financial analysis enables investors to assess whether such conditions can enhance community income, thereby aiding in the decision-making process regarding the allocation of capital for the economic upliftment of the community.